Penyuluhan Penyakit Tidak Menular (PTM) di Desa Adainasnosen Kabupaten Biak Numfor - Istyanto, Febry; Aswar , Sophian; Hermayani, Hermayani; Asih, Estu Sami; Ulfiani, Nurul; Rumbino, Maria Marice; Arwam, Anggaraymun H.M; Zaqiah, Anisah Nurul; Jumriati, Jumriati (Penerbit Goodwood, 2024)
Purpose: To educate and enhance the knowledge of the community in Adainasnosen village, located in Biak Numfor Regency, Papua Province, regarding the dangers of noncommunicable diseases (NCDs). Methodology: Planned and structured counseling sessions were conducted by lecturers and students, accompanied by simple laboratory tests for the Adainasnosen village community, including the examination parameters of Blood Pressure (BP), Uric Acid, Hemoglobin (Hb), Cholesterol, and Blood Sugar. Results: Some members of the village community were found to need an immediate change in lifestyle towards a healthier direction because several laboratory examination parameters were above normal levels. Regular counseling and examinations related to Non-Communicable Diseases (NCDs) must be implemented to effectively and comprehensively prevent these diseases. Limitations: Tools and materials fundamental for counseling inspections are limited. Hopefully, in the future, better inspection tools with a larger quantity can be utilized, enabling outreach to a greater number of village communities. Contribution: This inspection has benefits in raising awareness among the community in Adainanosen Village, Biak Numfor Regency, regarding the prevention of noncommunicable diseases.